In vivo epicardial force and strain characterisation in normal and MLP-knockout murine hearts. (9th June 2015) - Michaelides, M; Georgiadou, S; Constantinides, C
Abstract: The study's objective is to quantify in vivo epicardial force and strain in the normal and transgenic myocardium using microsensors. Male mice ( n = 39), including C57BL/6 ( n = 26), 129/Sv ( n = 5), wild-type (WT) C57 × 129Sv ( n = 5), and muscle LIM protein (MLP) knock-out ( n = 3), were studied under 1.5% isoflurane anaesthesia. Microsurgery allowed the placement of two piezoelectric crystals at longitudinal epicardial loci at the basal, middle, and apical LV regions, and the independent (and/or concurrent) placement of a cantilever force sensor. The findings demonstrate longitudinal contractile and relaxation strains that ranged between 4.8–9.3% in the basal, middle, and apical regions of C57BL/6 mice, and in the mid-ventricular regions of 129/Sv, WT, and MLP mice. Measured forces ranged between 3.1–8.9 mN. The technique's feasibility is also demonstrated in normal mice following afterload, occlusion–reperfusion challenges. Furthermore, the total mid-ventricular forces developed in MLP mice were significantly reduced compared to the WT controls (5.9 ± 0.4 versus 8.9 ± 0.2 mN, p < 0.0001), possibly owing to the fibrotic and stiffer myocardium. No significant strain differences were noted between WT and MLP mice. The possibility of quantifying in vivo force and strain from the normal murine heart is demonstrated with a potential usefulness in the characterisation of transgenic and diseased mice, where regional myocardial function may be significantly altered.